Liparis subgenus Menoneuron (Orchidaceae, Liparidinae) materials for taxonomic revision - Margońska, Hanna B. (Phytotaxa, 2017)
I present here taxonomic aspects of the genus Liparis subgenus Menoneuron which is restricted to South East Asia. This article gives all published names of this subgenus with their synonyms and the actual position of these taxa. Two new synonyms, 18 new lectotypes, four neotypes and one new representative of the subgenus are proposed.